Sequence Within A Sequence 2

Number Theory Level pending

Consider a sequence of numbers T 1 , T 2 , T 3 , , T n T_1, T_2, T_3, \ldots, T_n ( n Z + n\in \mathbb{Z}^+ ) that satisfies the following: T 1 = 5 , d 1 = 3 T_1=5, d_1=3 T 2 = T 1 + d 1 T 3 = T 2 + d 2 T n = T n 1 + d n 1 T_2=T_1+d_1 \\ T_3=T_2+d_2 \\ \vdots \\ T_n=T_{n-1}+d_{n-1} d k = d k 1 + 1 , k = 2 , 3 , 4 , , n 1 d_k=d_{k-1}+1,~~~k=2, 3, 4, \ldots, n-1

Denote S a = T 1 + T 2 + + T a S_a=T_1+T_2+\ldots+T_a , find S 153 S_{153} .


<<Sequence Within A Sequence

Sequence Within A Sequence 3>>


This is one part of 1+1 is not = to 3 .


The answer is 620925.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kenneth Tan
Mar 15, 2016

We have T 1 = T 1 T 2 = T 1 + d 1 T 3 = T 1 + d 1 + d 2 T n = T 1 + d 1 + d 2 + + d n 1 \begin{aligned} T_1&=T_1 \\ T_2&=T_1+d_1 \\ T_3&=T_1+d_1+d_2 \\ &\vdots \\ T_n&=T_1+d_1+d_2+\ldots+d_{n-1} \end{aligned} Add all these equations together, we have S n = n T 1 + i = 1 n 1 j = 1 i d j S_n=nT_1+\displaystyle \sum_{i=1}^{n-1}{\sum_{j=1}^i {d_j}} From the question we know that d 1 , d 2 , , d n 1 d_1, d_2, \ldots, d_{n-1} is an A.P. (Arithmetic Progression), suppose d k d k 1 = D , k = 2 , 3 , , n 1 d_k-d_{k-1}=D, ~~k=2,3,\ldots,n-1 , applying the sum of A.P. formula, we have j = 1 i d j = i 2 [ 2 d 1 + ( i 1 ) D ] \sum_{j=1}^i {d_j}=\frac {i}{2}[2d_1+(i-1)D] Hence, i = 1 n 1 j = 1 i d j = i = 1 n 1 i [ 2 d 1 + ( i 1 ) D ] 2 = 1 2 i = 1 n 1 [ ( 2 d 1 D ) i + D i 2 ] = 1 2 [ ( 2 d 1 D ) n ( n 1 ) 2 + D n ( n 1 ) ( 2 n 1 ) 6 ] = n ( n 1 ) 12 [ 6 d 1 3 D + 2 n D D ] = n ( n 1 ) [ 3 d 1 + ( n 2 ) D ] 6 \begin{aligned} \sum_{i=1}^{n-1}{\sum_{j=1}^i {d_j}}&=\sum_{i=1}^{n-1}{\frac {i[2d_1+(i-1)D]}{2}} \\ &=\frac {1}{2}\sum_{i=1}^{n-1}{[(2d_1-D)i+Di^2]} \\ &=\frac{1}{2}\left [\frac {(2d_1-D)n (n-1)}{2}+\frac {Dn (n-1)(2n-1)}{6}\right] \\ &=\frac {n (n-1)}{12}[6d_1-3D+2nD-D] \\ &=\frac {n (n-1)[3d_1+(n-2)D]}{6} \end{aligned} S n = n T 1 + n ( n 1 ) [ 3 d 1 + ( n 2 ) D ] 6 \therefore S_n=nT_1+\frac {n (n-1)[3d_1+(n-2)D]}{6} Now, substitute n = 153 n=153 , T 1 = 5 T_1=5 , d 1 = 3 d_1=3 , D = 1 D=1 , we could get S 153 = 620925 S_{153}=620925 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...